Noncommunicable diseases and risk factors in adult populations of several Pacific Islands: results from the WHO STEPwise approach to surveillance - Tara Kessaram; Jeanie McKenzie; Natalie Girin; Adam Roth; Paula Vivili; Gail Williams; Damian Hoy (Australian and New Zealand Journal of Public Health, 2015)
Abstract Objective: To provide an overview of the prevalence of noncommunicable diseases (NCDs) and their risk factors in several Pacific island countries and territories (PICTs), in accordance with global NCD targets. Methods: For six risk factors, data for adults (aged 25–64 years) from published reports of the World Health Organization STEPwise approach to NCD surveillance, or methodologically similar surveys, were collated, age standardised and compared across fifteen PICTs. Results: In the majority of PICT populations, more than half of male current drinkers drank heavily and more than 40% of men and 20% of women were current smokers. In 10 populations, about 50% or more of women were insufficiently physically active. Prevalence of hypertension and diabetes exceeded 20% and 25%, respectively, in several populations. Near or more than half of men and women in all populations were overweight; in most, more than one‐third of both sexes were obese. Conclusions: The prevalence of NCDs and risk factors varies widely between PICTs and by sex. The evidence shows the high and alarming present and future burden of NCDs in the region. Implications: Strengthened political commitment and increased investment are urgently required to tackle the NCD crisis, successfully achieve targets and ensure continuing sustainable development in the Pacific islands.